The heart-mind relationship in women cardiovascular primary prevention: the role of depression, anxiety, distress and Type-D personality in the 10-years cardiovascular risk evaluation - Giuliani, Mattia; Santagostino Baldi, Giulia; Capra, Nicolò; Bonomi, Alice; Marzorati, Chiara; Sebri, Valeria; Guiddi, Paolo; Montorsi, Piero; Pravettoni, Gabriella; Trabattoni, Daniela (Frontiers in Cardiovascular Medicine, 2024)
Introduction Cardiovascular diseases are the leading cause of death among women. Prevention programmes underscore the need to address women-specific risk factors. Additionally, mental well-being is a significant aspect to consider when grappling with cardiovascular disease in women, particularly depression, anxiety, distress, and personality traits. This study aimed to create “at-risk” psychological profiles for women without prior cardiovascular disease history and to evaluate the association between anxiety, depression, distress, and Type-D personality traits with increased cardiovascular risk over 10 years. Methods 219 women voluntarily participated in the “Monzino Women's Heart Centre” project for primary prevention and early diagnosis of cardiovascular diseases. Psychological profiles were developed utilising cluster analysis. Results The primary finding indicating that belonging to the “at-risk” psychological cluster was associated with a surge in the 10-year cardiovascular risk prediction score, despite the number of comorbid risk factors (Psychological “at-risk” cluster: β = .0674; p = .006; Risk factors: β = .0199; p = .242). Conclusions This finding suggests that psychological well-being of women should be assessed from the very beginning of cardiovascular prevention programmes.